Seroprevalence of Anti-S1-RBD Antibodies in Pre-pandemic and Pandemic Subjects From Hail Region, KSA - Sherwani, Subuhi; Khan, Mohd Wajid Ali; Mallik, Arshi; Khan, Mahvish; Saleem, Mohd; Raafat, Mohamed; Shati, Ayed A.; Alam, Noor (Frontiers in Public Health, 2022)
Background Two years into the pandemic, yet the threat of new SARS-CoV-2 variants continues to loom large. Sustained efforts are required to fully understand the infection in asymptomatic individuals and those with complications. Identification, containment, care, and preventative strategies rely on understanding the varied humoral immune responses. Methods An in-house ELISA was developed and standardized to screen for serum IgG antibodies against the SARS-CoV-2 S1-RBD protein as an antigen. This study aims to investigate the seroprevalence of serum antibodies against S1-RBD antigen in pre-pandemic (n = 120) and during the early pandemic period (n = 120) in subjects from the Hail region, KSA and to correlate it with clinical and demographic factors. Results Samples collected from both male (n = 60) and female (n = 60) subjects during the pandemic in the age groups of 20–40 (0.31 ± 0.029 and 0.29 ± 0.024, respectively) and 41–60 years (0.35 ± 0.026 and 0.30 ± 0.025, respectively) showed significantly higher levels of serum antibodies against S-RBD antigen than the age-matched pre-pandemic samples [male (n = 60) and female (n = 60)]. Pandemic subjects exhibited significantly (p < 0.01) higher inhibition (80–88%) than age-matched pre-pandemic subjects (32–39%). Antibodies against S1-RBD antigen were detected in approximately 10% of the total pre-pandemic population (males and females). However, subjects > 60 years did not show antibodies. Conclusion Antibody levels increased in samples collected during the pandemic, even though these subjects were not clinically COVID-19 positive. A small number of pre-pandemic subjects showed serum antibodies, suggesting prior exposure to other coronaviruses in the region. With dwindling neutralizing antibody levels and reduced vaccine efficacy against newer variants, it remains crucial to develop better assays for surveillance, management, and future research.